Nanocomposite silica surfactant microcapsules by evaporation induced self assembly: tuning the morphological buckling by modifying viscosity and surface charge - Sen, D.; Bahadur, Jitendra; Mazumder, S.; Verma, G.; Hassan, P. A.; Bhattacharya, S.; Vijai, K.; Doshi, Pankaj (Soft Matter, 2012)
Nanocomposite microcapsules of silica and surfactants have been synthesized using evaporation induced self-assembly through spray drying. It was established using electron microscopy and small-angle neutron/X-ray scattering experiments that the viscosity of the virgin dispersion and surface charge of colloidal components play a significant role in the buckling of spray droplets during drying. Hollow spherical grains are realized at relatively low viscosity and higher surface charge while mushroom like grains manifest at higher viscosity and lower surface charge. In the intermediate conditions, deformed doughnut shaped microcapsules are obtained. Scattering experiments establish the presence of the organization of micelle like aggregates of surfactants in the dried grains and also corroborate with the observations from electron microscopy. A plausible mechanism regarding the chronological pathways of morphological transformation is illustrated. Computer simulation, based on buckling of an elastic shell using a surface evolver, has been attempted in order to corroborate the experimental results.

Necking in extrusion film casting: the role of macromolecular architecture - Pol, Harshawardhan V.; Thete, Sumeet Suresh; Doshi, Pankaj; Lele, Ashish K. (Journal of Rheology, 2013)
Extrusion film casting (EFC) is used on an industrial scale to produce several thousand tons of polymer films and coatings. While significant research has been carried out on necking of films of viscoelastic melts in EFC, the influence of macromolecular chain architecture on the necking behavior is not yet fully understood. In the present research, we have explored experimentally and theoretically the effects of long chain branching and molecular weight distribution on the extent of necking during EFC. Polyethylenes of essentially linear architecture but having narrow and broad molecular weight distributions, and polyethylenes having long chain branching were used for experimental studies. The EFC process was analyzed using the one-dimensional flow model of Silagy et al. [Polym. Eng. Sci. 36(21), 2614-2625 (1996)] in which multimode molecular constitutive equations namely the ``extended pom-pom'' equation (for long chain branched polymer melts) and the ``Rolie-Poly (Rouse linear entangled polymers)'' equation (for linear polymer melts) were incorporated. We show that the model qualitatively captures the salient features of the experimental data thereby elucidating the role of chain architecture on the extent of necking. (C) 2013 The Society of Rheology. [http://dx.doi.org/10.1122/1.4788911]

Flow of granular matter in a silo with multiple exit orifices: jamming to mixing - Kamath, Sandesh; Kunte, Amit; Doshi, Pankaj; Orpe, Ashish V. (Physical Review E, 2014)
We investigate the mixing characteristics of dry granular material while draining down a silo with multiple exit orifices. The mixing in the silo, which otherwise consists of noninteracting stagnant and flowing regions, is observed to improve significantly when the flow through specific orifices is stopped intermittently. This momentary stoppage of flow through the orifice is either controlled manually or is chosen by the system itself when the orifice width is small enough to cause spontaneous jamming and unjamming. We observe that the overall mixing behavior shows a systematic dependence on the frequency of closing and opening of specific orifices. In particular, the silo configuration employing random jamming and unjamming of any of the orifices shows early evidence of chaotic mixing. When operated in a multipass mode, the system exhibits a practical and efficient way of mixing particles.

Modeling chain-end scission using the fixed pivot technique - Ho, Yong Kuen; Doshi, Pankaj; Yeoh, Hak Koon; Ngoh, Gek Cheng (Chemical Engineering Science, 2014)
Chain-end scission of polymer molecules is the breakage of a fixed-size oligomer or monomer from either end of the macromolecule. A common example is the generation of the glucose monomer from the hydrolysis of starch by glucoamylase. Modeling the dynamics of chain-end scission from first principles by considering each molecular size is challenging due to the large number of differential equations to be solved. The Population Balance Modeling (PBM) is a helpful framework as it could be formulated to lump a few molecular sizes together. However, it is then not obvious how to accurately account for the temporal evolution of the low molecular weight species, which is often of the greatest industrial interest. Here, the Fixed Pivot (FP) technique - one of the methods to solve PBM equations was appropriately modified to address this difficulty. By treating the lower molecular size range as a discrete domain in conjunction with a continuous domain in the upper ranges, the modified FP technique not only retains its original strengths, but also captures accurately the distribution of oligomers including the monomer. The results, which were obtained at a fraction of computational expense, benchmarked very well against the exact solutions for a polymer with a broad size distribution at different Degrees of Polymerization up to similar to O(10(5)). To facilitate wider adoption, guidelines on choice of pivots and observations of the performance of the modified FP technique are also deliberated. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Chain-end scission; Fixed Pivot; Polymers; Population balance

Nonisothermal analysis of extrusion film casting process using molecular constitutive equations - Pol, Harshawardhan; Banik, Sourya; Azad, Lal Busher; Thete, Sumeet Suresh; Doshi, Pankaj; Lele, Ashish K. (Rheologica Acta, 2014)
Extrusion film casting (EFC) is a commercially important process that is used to produce several thousand tons of polymer films and coatings. In a recent work, we demonstrated the influence of polymer chain architecture on the extent of necking in an isothermal film casting operation (Pol et al., J Rheol 57:559-583, 2013). In the present research, we have explored experimentally and theoretically the effects of long-chain branching on the extent of necking during nonisothermal film casting conditions. Polyethylenes of linear and long-chain branched architectures were used for experimental studies. The EFC process was analyzed using the 1-D flow model of Silagy et al. (Polym Eng Sci 36:2614-2625, 1996) in which the energy equation was introduced to model nonisothermal effects, and two multimode constitutive equations, namely the ``extended pom-pom'' (XPP, for long-chain branched polymer melts) equation and the ``Rolie-Poly stretch version'' (RP-S, for linear polymer melts) equation, were incorporated to account for the effects of polymer chain architecture. We show that the model does a better job of capturing the qualitative features of the experimental data, thereby elucidating the role of chain architecture and nonisothermal conditions on the extent of necking.
Keywords: Branched; Extrusion; Film; Linear; Necking; Nonisothermal; Polyethylene

Spontaneous jamming and unjamming in a hopper with multiple exit orifices - Kunte, Amit; Doshi, Pankaj; Orpe, Ashish V. (Physical Review E, 2014)
We show that the flow of granular material inside a two-dimensional flat bottomed hopper is altered significantly by having more than one exit orifice. For hoppers with small orifice widths, intermittent flow through one orifice enables the resumption of flow through the adjacent jammed orifice, thus displaying a sequence of jamming and unjamming events. Using discrete element simulations, we show that the total amount of granular material (i.e., avalanche size) emanating from all the orifices combined can be enhanced by about an order of magnitude difference by simply adjusting the interorifice distance. The unjamming is driven primarily by fluctuations alone when the interorifice distance is large, but when the orifices are brought close enough, the fluctuations along with the mean flow cause the flow to unjam.

Dripping dynamics of newtonian liquids from a tilted nozzle - Taur, Amaraja; Doshi, Pankaj; Yeoh, Hak Koon (European Journal of Mechanics B-Fluids, 2015)
The dripping dynamics of Newtonian liquids emanating from an inclined nozzle is studied. The fluid viscosity mu flow rate Q, nozzle radius R, and inclination angle theta have been varied independently. The drop breakup times and the different modes of dripping have been identified using high speed imaging. A phase diagram showing the transition between the dripping modes for different theta is constructed in the (We, Ka) space, where We (Weber number) measures the relative importance of inertia to surface tension force and Ka (Kapitza number) measures the relative importance of viscous to surface tension forces. At low values of We and Ka, the system shows a transition from period-1 to limit cycle before chaos. The limit cycle region narrows down with increase in inclination. Further increase in the values of We and Ka gives a direct transition from period-1 to chaos. The new experiments reveal that in the period-1 region, increasing the nozzle inclination angle theta results in lowering of the drop breakup time t(b), suggesting that the surface tension forces cannot hold the drops longer despite the weakened effective gravitational pull. This counter-intuitive finding is further corroborated by pendant drop experiments and computations. More curiously, throughout the period-1 regime, the drop volume is independent of the flow rate. This resulted in a relatively simple correlation for the dimensionless drop volume V = 1.3G(-1)Ka(0.02)(cos theta)(0.37) accurate to within 10% over wide ranges of the independent variables. (C) 2014 Elsevier Masson SAS. All rights reserved.
Keywords: Asymmetric dripping; Breakup time; Drop volume; Inclined nozzle; Phase diagram

Extrusion film casting of long chain branched polypropylene - Chikhalikar, Kalyani; Banik, Sourya; Azad, Lal Busher; Jadhav, Kishor; Mahajan, Sunil; Ahmad, Zubair; Kulkarni, Surendra; Gupta, Surendra; Doshi, Pankaj; Pol, Harshawardhan; Lele, Ashish K. (Polymer Engineering and Science, 2015)
Extrusion film casting (EFC) is an important melt processing operation which is extensively used to make polypropylene (PP) films. Linear PP shows significant amount of necking and draw resonance during EFC. One of the ways to reduce necking is to introduce long chain branches (LCB) on the polymer backbone. The long branches impart extensional strain hardening behavior thereby stabilizing the melt flow. In this work, we investigate the influence of long chain branching in polypropylene on the extent of necking in the EFC process. Laboratory scale EFC experiments were performed on homopolymer PP of linear and long chain branched architectures. Simulations of the EFC process were carried out using the one-dimensional flow model of Silagy et al., Polym. Eng. Sci.,36, 2614 (1996) into which we incorporate two different multi-mode molecular constitutive equations namely, the eXtended Pom-Pom' equation (XPP, for long chain branched PP) and the Rolie-Poly' equation (RP-S, for linear PP). Our experimental data confirm that presence of long chain branching in PP reduces the extent of necking and our numerical predictions show qualitative agreement with experimental data, thereby elucidating the role of chain architecture on the extent of necking. POLYM. ENG. SCI., 55:1977-1987, 2015. (c) 2014 Society of Plastics Engineers

Influence of macromolecular architecture on necking in polymer extrusion film casting process - Pol, Harshawardhan V.; Banik, Sourya; Azad, Lal Busher; Thete, Sumeet; Doshi, Pankaj; Lele, Ashish (30th International Conference of the Polymer-Processing-Society (PPS), 2015)
Extrusion film casting (EFC) is an important polymer processing technique that is used to produce several thousand tons of polymer films/coatings on an industrial scale. In this research, we are interested in understanding quantitatively how macromolecular chain architecture (for example long chain branching (LCB) or molecular weight distribution (MWD or PDI)) influences the necking and thickness distribution of extrusion cast films. We have used different polymer resins of linear and branched molecular architecture to produce extrusion cast films under controlled experimental conditions. The necking profiles of the films were imaged and the velocity profiles during EFC were monitored using particle tracking velocimetry (PTV) technique. Additionally, the temperature profiles were captured using an IR thermography and thickness profiles were calculated. The experimental results are compared with predictions of one-dimensional flow model of Silagy et al(1) wherein the polymer resin rheology is modeled using molecular constitutive equations such as the Rolie-Poly (RP) and extended Pom Pom (XPP). We demonstrate that the 1-D flow model containing the molecular constitutive equations provides new insights into the role of macromolecular chain architecture on film necking. D-1. Silagy, Y. Demay, and J-F. Agassant, Polym. Eng. Sci., 36, 2614 (1996).

Interlinked population balance and cybernetic models for the simultaneous saccharification and fermentation of natural polymers - Ho, Yong Kuen; Doshi, Pankaj; Yeoh, Hak Koon; Ngoh, Gek Cheng (Biotechnology and Bioengineering, 2015)
Simultaneous Saccharification and Fermentation (SSF) is a process where microbes have to first excrete extracellular enzymes to break polymeric substrates such as starch or cellulose into edible nutrients, followed by in situ conversion of those nutrients into more valuable metabolites via fermentation. As such, SSF is very attractive as a one-pot synthesis method of biological products. However, due to the co-existence of multiple biochemical steps, modeling SSF faces two major challenges. The first is to capture the successive chain-end and/or random scission of the polymeric substrates over time, which determines the rate of generation of various fermentable substrates. The second is to incorporate the response of microbes, including their preferential substrate utilization, to such a complex broth. Each of the above-mentioned challenges has manifested itself in many related areas, and has been competently but separately attacked with two diametrically different tools, i.e., the Population Balance Modeling (PBM) and the Cybernetic Modeling (CM), respectively. To date, they have yet to be applied in unison on SSF resulting in a general inadequacy or haphazard approaches to examine the dynamics and interactions of depolymerization and fermentation. To overcome this unsatisfactory state of affairs, here, the general linkage between PBM and CM is established to model SSF. A notable feature is the flexible linkage, which allows the individual PBM and CM models to be independently modified to the desired levels of detail. A more general treatment of the secretion of extracellular enzyme is also proposed in the CM model. Through a case study on the growth of a recombinant Saccharomyces cerevisiae capable of excreting a chain-end scission enzyme (glucoamylase) on starch, the interlinked model calibrated using data from the literature (Nakamura et al., Biotechnol. Bioeng. 53:21-25, 1997), captured features not attainable by existing approaches. In particular, the effect of various enzymatic actions on the temporal evolution of the polymer distribution and how the microbes respond to the diverse polymeric environment can be studied through this framework. Biotechnol. Bioeng. 2015;112: 2084-2105. (c) 2015 Wiley Periodicals, Inc.
Keywords: cybernetic modeling; population balance modeling; simultaneous saccharification and fermentation

Self-similar rupture of thin free films of power-law fluids - Thete, Sumeet Suresh; Anthony, Christopher; Basaran, Osman A.; Doshi, Pankaj (Physical Review E, 2015)
The rupture of a thin free film of a power-law fluid under the competing influences of destabilizing van der Waals pressure and stabilizing surface tension pressure is analyzed. In such a fluid, viscosity decreases with the deformation rate raised to the n - 1 power where 0 < n <= 1 (n = 1 for a Newtonian fluid). When 6/7 < n <= 1, film rupture occurs under a balance between van der Waals pressure, inertial stress, and viscous stress. When n < 6/7, however, the dominant balance changes: Viscous stress becomes negligible and the film ruptures under the competition between van der Waals pressure, inertial stress, and surface tension pressure.

Fingering instability in the flow of a power-law fluid on a rotating disc - Arora, Akash; Doshi, Pankaj (Physics of Fluids, 2016)
A computational study of the flow of a non-Newtonian power law fluid on a spinning disc is considered here. The main goal of this work is to examine the effect of non-Newtonian nature of the fluid on the flow development and associated contact line instability. The governing mass and momentum balance equations are simplified using the lubrication theory. The resulting model equation is a fourth order non-linear PDE which describes the spatial and temporal evolutions of film thickness. The movement of the contact line is modeled using a constant angle slip model. To solve this moving boundary problem, a numerical method is developed using a Galerkin/finite element method based approach. The numerical results show that the spreading rate of the fluid strongly depends on power law exponent n. It increases with the increase in the shear thinning character of the fluid (n < 1) and decreases with the increase in shear thickening nature of the fluid (n > 1). It is also observed that the capillary ridge becomes sharper with the value of n. In order to examine the stability of these ridges, a linear stability theory is also developed for these power law fluids. The dispersion relationship depicting the growth rate for a given wave number has been reported and compared for different power-law fluids. It is found that the growth rate of the instability decreases as the fluid becomes more shear thinning in nature, whereas it increases for more shear thickening fluids. (C) 2016 AIP Publishing LLC.

Fingering instability of a suspension film spreading on a spinning disk - Kulkarni, Mayuresh; Sahoo, Subhadarshinee; Doshi, Pankaj; Orpe, Ashish V. (Physics of Fluids, 2016)
The spreading of a thin film of suspension on a spinning disk and the accompanying contact line instability is studied through flow visualization experiments. The critical radius for the onset of instability shows an increase with increase in the particle fraction (phi(p)) before decreasing slightly at the highest value of phi(p) studied, while the instability wavelength (lambda) exhibits a non-monotonic dependence. The value of lambda is close to that for a partially wetting liquid at lower phi(p), it decreases with increasing phi(p) to a minimum before increasing again at largest phi(p). The non-monotonic trends observed for lambda are discussed in light of the linear stability analysis of thin film equations derived for suspensions by Cook et al. [''Linear stability of particle-laden thin films,'' Eur. Phys. J.: Spec. Top. 166, 77 (2009)] and Balmforth et al. [''Surface tension driven fingering of a viscoplastic film,'' J. Non Newtonian Fluid Mech. 142, 143 (2007)]. Published by AIP Publishing.

Two-layer spin coating flow of newtonian liquids: a computational study - Sahoo, Subhadarshinee; Arora, Akash; Doshi, Pankaj (Computers & Fluids, 2016)
Spin coating is the most commonly used method in industries to form coating films of desired thickness and functionality. In case of two-layer spin coating process, stratified layers of two immiscible liquids are deposited onto the substrate simultaneously, which spread and thin to form two-layer coating film of finite thickness. Questions concerning the effect of surface/interfacial tension on uniformity of these films and contact line evolution are relevant and need thorough investigation. Therefore, an axisymmetric model governing the flow of two-layer spin coating process is developed here. Liquids used for the study are assumed to be Newtonian and fully wetting. The contact line singularity is resolved using a precursor layer model and the governing equations are simplified using lubrication approximation. A Galerkin finite-element method (G/FEM) based scheme is developed to solve the resulting fourth order non-linear PDEs. Simulation results reveal that the fluid properties like ratio of the viscosity of upper layer fluid to lower layer and ratio of the upper gas-liquid surface tension to inner liquid-liquid interfacial tension have profound impact on the time evolution of the film profile, contact radius and shape of the capillary ridges. It is observed that a uniform two-layer film surrounded by thin single layer film is formed when the viscosity ratio is small. On the contrary, when viscosity ratio is large, a thin two-layer film surrounded by bulky capillary ridges is formed. Similarly, the results also show that sharpness of capillary ridge increases with decrease in the surface tension ratio. Further, it is found that increase in the precursor layer thickness increases the spreading rate, thereby making the film more uniform. Finally, the uniformity of the final two-layer film does not get affected by the initial volume of fluid present in the upper layer. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Axisymmetric flow; Mathematical modeling; Multi-layer coating; Precursor layer model; Thin-film flow; Two-layer spin coating

Capillary uptake in macroporous compressible sponges - Chatterjee, Soumyajyoti; Doshi, Pankaj; Kumaraswamy, Guruswamy (Soft Matter, 2017)
The capillarity-driven uptake of liquid in swellable, highly porous sponges is of significant industrial importance. Sponges prepared using polymers and their composites with carbon nanotubes and graphene have been reported, with extraordinary solvent uptake capacities and with the ability to separate oil from water. However, the effect of systematic variation of sponge characteristics on solvent uptake has not been investigated. Here, we report experiments that study capillary uptake in a variety of flexible, centimetre-sized macroporous cylindrical sponges. We used ice-templating to prepare a series of model macroporous sponges in which the porosity, modulus and composition were systematically varied. We investigated two kinds of sponge: (a) those composed purely of cross-linked polymers and (b) those prepared as composites of inorganic particles and polymers. Both kinds of sponge are flexible and exhibit elastic recovery after large compressive deformation. All sponges were characterized thoroughly with respect to their pore microstructure and elastic modulus. When one end of a sponge is plunged into a large reservoir, water rises through capillary action against gravity. We observed a transition from an inertial capillary regime, where the liquid column height rose linearly with time, t, to a viscous capillary regime, where the liquid height rose with time t(0.5). We showed that these results can be rationalized using analyses developed for rigid sponges. We combined differential momentum balance equations for uptake in rigid capillaries with the phenomenological Ergun-Forchheimer relations to account for the effect of the sponge microstructure. This approach works remarkably well in the viscous capillary regime and shows that capillary uptake is governed primarily by the total porosity and pore dimensions of soft sponges.
Keywords: aerogels; Building blocks; Catalyst Supports; Contact-angels; Dynamics; flow; Organic Liquids; Porous-Media; Rise

Effect of viscoelastic relaxation modes on stability of extrusion film casting process modeled using multi-mode Phan-Thien-Tanner constitutive equation - Dhadwal, Renu; Banik, Sourya; Doshi, Pankaj; Pol, Harshawardhan (Applied Mathematical Modelling, 2017)
Extrusion film casting (EFC) is a commercially important process that is used to produce a significant quantity of polymer films, sheets and coatings for both industrial and household applications. Recently, we have demonstrated the influence of polymer chain architecture on the extent of necking under isothermal as well as non-isothermal film casting operation for commercially relevant polyolefin based materials [1-4]. In the present research, we focus on another instability that frequently occurs in high-speed EFC process called as draw resonance. Draw resonance manifests itself as an instability that causes periodic fluctuations in both the width as well as thickness of the extruded molten film above a critical draw ratio (DR). In this work, we have carried out a linear stability analysis of the isothermal EFC process using a multi-mode Phan-Thien-Tanner (PTT) constitutive equation to determine the onset of draw resonance. We show that as the number of relaxation modes is increased there is a dramatic change in the stability regions. In particular, there is a marked variation in the stability regions obtained by Simulating the multi-mode model and those obtained by taking averaged relaxation time of the modes. Additionally, as the number of faster-relaxing modes in a multi-mode spectrum is progressively increased, the process becomes increasingly stable as the level of elasticity in the melt decreases. Finally, the addition of a long relaxation mode in a multi-mode spectrum is akin to adding a long chain branch to a linear polymer that leads to a reduction in film necking and in many cases to enhanced process stability. (C) 2017 Elsevier Inc. All rights reserved.

New insights into the use of multi-mode phenomenological constitutive equations to model extrusion film casting process - Thete, Sumeet S.; Doshi, Pankaj; Pol, Harshawardhan V. (Journal of Plastic Film & Sheeting, 2017)
This article is concerned with the effect of the individual viscoelastic relaxation modes of a polymer melt on its behavior in polymer melt extrusion film casting process. We compare the predicted versus experimentally obtained film necking or neck-in profile as a function of draw ratio. The predicted necking profile was obtained using well-established one-dimensional isothermal flow kinematics and consisted of using two different phenomenological constitutive equations, upper convected Maxwell and Phan-Thien-Tanner, with a discrete spectrum of relaxation times. The numerical simulations, containing the two different phenomenological constitutive equations, provided an insight into the effect of the slow and the fast relaxing modes on the stresses, strains, and strain/extensional rates that develop in the molten polymer film as it is stretched from the die exit to the chill-roll. The slow relaxing modes follow trends that are directly proportional to strain (similar to Hookean solids), whereas the fast relaxing modes follow trends that are directly proportional to the stretch rate (in accordance with Newton's law of viscosity). Comparing the numerical predictions with the experiments showed that predictions using the upper convected Maxwell constitutive equation best described the long-chain branched polymers (like low-density polyethylene, which shows extensional strain hardening) in the extrusion film casting process. On the other hand, predictions using the Phan-Thien-Tanner constitutive equation best described the linear polymers (like linear low-density polyethylene, which does not show noticeable extensional strain hardening) in the extrusion film casting process.

Spreading dynamics of superposed liquid drops on a spinning disk - Sahoo, Subhadarshinee; Orpe, Ashish V.; Doshi, Pankaj (Physics of Fluids, 2018)
We have experimentally studied simultaneous spreading of superposed drops of two Newtonian liquids on top of a horizontal spinning disk using the flow visualization technique. An inner drop of high surface tension liquid is placed centrally on the disk followed by a drop of outer liquid (lower surface tension) placed exactly above that. The disk is then rotated at a desired speed for a range of volume ratios of two liquids. Such an arrangement of two superposed liquid drops does not affect the spreading behavior of the outer liquid but influences that of the inner liquid significantly. The drop spreads to a larger extent and breaks into more fingers (Nf) as compared to the case where the same liquid is spreading in the absence of outer liquid. The experimentally observed number of fingers is compared with the prediction using available theory for single liquid. It is found that the theory over-predicts the value of Nf for the inner liquid while it is covered by an outer liquid. We provide a theoretical justification for this observation using linear stability analysis. Our analysis demonstrates that for small but finite surface tension ratio of the two liquids, the presence of the outer interface reduces the value of the most unstable wave number which is equivalent to the decrease in the number of fingers observed experimentally. Finally, sustained rotation of the disk leads to the formation of droplets at the tip of the fingers traveling outwards. Published by AIP Publishing.

Friction-mediated flow and jamming in a two-dimensional silo with two exit orifices - Orpe, Ashish V.; Doshi, Pankaj (Physical Review E, 2019)
We show that the interparticle friction coefficient significantly influences the flow and jamming behavior of granular materials exiting through the orifice of a two-dimensional silo in the presence of another orifice located in its vicinity. The fluctuations emanating from a continuous flow through a larger orifice results in an intermittent flow through the smaller orifice consisting of sequential jamming and flowing events. The mean time duration of jammed and flow events, respectively, increase and decrease monotonically with increasing interparticle friction coefficient. The frequency of unjamming instances (n(u)), however, shows a nonmonotonic behavior comprising an increase followed by a decrease with increasing friction coefficient. The decrease on either side of the maximum, then, represents a system moving progressively towards a permanently jammed or a permanently flowing state. The overall behavior shows a systematic dependence on the interorifice distance, which determines the strength of the fluctuations reaching the smaller orifice leading to unjamming instances. The probability distributions of jamming and flowing times are nearly similar for different combinations of friction coefficients and interorifice distances studied and, respectively, exhibit exponential and power-law tails.

Flow of lubricated granular material on an inclined plane - Ghodake, Ravindra S.; Doshi, Pankaj; Orpe, V. Ashish (Powder Technology, 2022)
We have studied the gravity driven flow of spherical shaped, millimetric sized granular material coated with aspherical, micron-sized, near frictionless lubricant particles. Experiments were performed on an inclined plane using two different sized particles for varying concentrations of the lubricant. The particle volumetric flow rate exhibits a non-monotonic behavior with increasing lubricant concentration. It shows an increase at lower lubricant concentration followed by a decrease at higher lubricant concentration. The lubricant particles adhere to the granular particle surface thereby reducing the inter-particle friction. However, presence of lubricant particles at higher concentration damps out inter-particle collision thereby reducing the inter-particle momentum transfer. Non-monotonicity in the observed behavior is then conjectured to arise due to competing effects of inter-particle friction and inter-particle collision. The present work and the overall observed behavior therein provides a simple experimental system to characterize the effects of added lubricant material in pharmaceutical and other relevant industrial applications.
Keywords: Friction; granular; Inclined plane; Lubrication; Powder

Flow and clogging behavior of a mixture of particles in a silo - Bhure, Sukhada C.; Doshi, Pankaj; Orpe, Ashish V. (Physics of Fluids, 2024)
We investigated the clogging behavior observed during the flow of aspherical particles from a silo in the presence of spherical particles of different sizes and proportions using flow visualization experiments and discrete element method simulations. The size of the avalanche, essentially the tendency of clogging, exhibits non-monotonic dependence on the spherical particle volume fraction. For small enough content of spherical particles, the clogging tendency intensifies, whereas it reduces rapidly for high enough spherical particle fractions, with a minimum in between. The non-monotonic behavior is observed to persist over for different spherical particle sizes. The overall behavior is shown to arise due to competing effects between the localized total particle fraction influencing avalanche strength and mean size of the particles exiting the silo, influencing the probability of arch formation.